FORMULATION OF POVERTY INDICATORS AND MEASUREMENT OF COMMUNITY WELFARE IN PAGEDANGAN ILIR VILLAGE, KRONJO DISTRICT, TANGERANG REGENCY - Achmad Reza Widjaja; Seli Meylinda (Universitas Prof. Dr. Moestopo (Beragama), 2021)
Apparatus of Pagedangan Ilir village who do not use standard indicators for the determination of pre-prosperous families and the absence of specific indicators owned by Pagedangan Ilir Village. It will have an impact on the targeting of beneficiaries of a welfare program, thus it will to make the community welfare program less effective.This research aims to formulate indicators of poverty and measurement of community welfare in Pagedangan Ilir Village. The formulation of poverty indicators and measurements of welfare is a review of various poverty indicators or standard welfare measures from government institutions and past researches. In this paper, the research that has been conducted by Center for International Forestry Research (CIFOR) becomes the basic benchmark to measure the welfare of the community in Pagedangan Ilir Village, with the results obtained in the form of welfare based on indicators index, dimension index and aggregate index. The results of the research showed that in aggregate, there were no families in Pagedangan Ilir Village classified as